Alteration of water absorption in the THz region traces the onset of fibrillation in proteins. Issue 8 (5th January 2021) - Pyne, Partha; Samanta, Nirnay; Gohil, Himanshu; Prabhu, S. S.; Mitra, Rajib Kumar
Abstract : Using terahertz spectroscopy, we established the alteration of the collective hydration of water during the fibrillation process (native → intermediate → fibril) of a model protein bovine serum albumin. Abstract : Using terahertz spectroscopy, we established the alteration of the collective hydration of water during the fibrillation process (native → intermediate → fibril) of a model protein bovine serum albumin. This label-free study concludes that water dynamics change systematically with protein conformational changes as it experiences a hydrophobic environment during the initial protein unfolding process, followed by the release of bound water during oligomerization and finally the hydrophobic interior of the fibril.